THE RELATIONSHIP OF TEACHERS’ PERCEPTIONS TOWARDS ORGANIZATIONAL CLIMATE AND THEIR RETENTION IN HUIMIN WENCHANG HIGH SCHOOL, SHANDONG PROVINCE, CHINA - LIU, TIANTIAN; VINITWATANAKHUN, WATANA (Scholar: Human Sciences, 2022)
This research sought to study the relationship between teachers’ perceptions of school climate and their retention in Huimin Wenchang High School in Binzhou City, Shandong Province, China. To this end, the study assessed teachers’ perceptions of the school’s climate and their level of needs, using the mean and standard deviation for descriptive and quantitative analysis. Finally, the Pearson product-moment correlation coefficient analysis analyzes and evaluates the relationship between these two variables. It was conducted in the 2020 academic year, with 48 full-time teachers participating and a return rate of 100% in the total target population of 48 teachers. Statistics showed that the significance of Pearson’s correlation coefficient is .000, and R-value is .849. The results showed that Huimin Wenchang High School teachers in Binzhou City, Shandong Province, had high awareness and positive attitudes towards the school atmosphere. And there is a strong positive correlation between the teacher retention rate and the teacher’s perceptions of the teacher’s organizational climate.